Childhood exposure to ambient polycyclic aromatic hydrocarbons is linked to epigenetic modifications and impaired systemic immunity in T cells. Issue 1 (January 2015) - Hew, K. M.; Walker, A. I.; Kohli, A.; Garcia, M.; Syed, A.; McDonald‐Hyman, C.; Noth, E. M.; Mann, J. K.; Pratt, B.; Balmes, J.; Hammond, S. Katharine; Eisen, E. A.; et al.
Summary Background Evidence suggests that exposure to polycyclic aromatic hydrocarbons (PAHs) increases atopy; it is unclear how PAH exposure is linked to increased severity of atopic diseases. Objective We hypothesized that ambient PAH exposure is linked to impairment of immunity in atopic children (defined as children with asthma and/or allergic rhinitis) from Fresno, California, an area with elevated ambient PAHs. Methods We recruited 256 subjects from Fresno, CA. Ambient PAH concentrations (ng/m3) were measured using a spatial‐temporal regression model over multiple time periods. Asthma diagnosis was determined by current NHLBI criteria. Phenotyping and functional immune measurements were performed from isolated cells. For epigenetic measurements, DNA was isolated and pyrosequenced. Results We show that higher average PAH exposure was significantly associated with impaired Treg function and increased methylation in the forkhead box protein 3 (FOXP3) locus (P < 0.05), conditional on atopic status. These epigenetic modifications were significantly linked to differential protein expression of FOXP3 (P < 0.001). Methylation was associated with cellular functional changes, specifically Treg dysfunction, and an increase in total plasma IgE levels. Protein expression of IL‐10 decreased and IFN‐γ increased as the extent of PAH exposure increased. The strength of the associations generally increased as the time window for average PAH exposure increased from 24 hr to 1 year, suggesting more of a chronic response. Significant associations with chronic PAH exposure and immune outcomes were also observed in subjects with allergic rhinitis. Conclusions and Clinical Relevance Collectively, these results demonstrate that increased ambient PAH exposure is associated with impaired systemic immunity and epigenetic modifications in a key locus involved in atopy: FOXP3, with a higher impact on atopic children. The results suggest that increased atopic clinical symptoms in children could be linked to increased PAH exposure in air pollution.